Neighbour Programme: The Mixture of Southeast Asian Visual Culture - Hanny Wijaya (Humaniora, 2014)
Neighbour Programme was initiated in 2010 by three institutions from Southeast Asia: Singapore, Malaysia, and Thailand; then Indonesia joined them a year later in 2011. These institutions, which specialise in art and design, decided to develop a project about cultural exchange that aimed to reconnect art and design in the form of a dialogue and research as practice. This project also intended to include forming mutual networks to organise exchange programmes, creating cultural collisions within this mixture. Based on thought that Southeast Asia’s countries have the same root of art, culture and heritage, Neighbour focused on searching a different topic each year that could be explored and developed into knowledge and understanding for both students and lecturers, and hopefully to publics about their own visual culture. Neighbour has running since 2010 and still developing until present. This project has used different methods, such as Constructivist Learning that gave new perspective of gaining knowledge; and hopefully Neighbour will keep trying to find a new method to engage art, design, and culture with publics internationally.